Whole tissue and single cell mechanics are correlated in human brain tumors - Sauer, Frank; Fritsch, Anatol; Grosser, Steffen; Pawlizak, Steve; Kiessling, Tobias; Reiss-Zimmermann, Martin; Shahryari, Mehrgan; Mueller, Wolf C.; Hoffmann, Karl-Titus; Kaes, Josef A.; Sack, Ingolf (Soft Matter, 2021)
Biomechanical changes are critical for cancer progression. However, the relationship between the rheology of single cells measured ex-vivo and the living tumor is not yet understood. Here, we combined single-cell rheology of cells isolated from primary tumors with in vivo bulk tumor rheology in patients with brain tumors. Eight brain tumors (3 glioblastoma, 3 meningioma, 1 astrocytoma, 1 metastasis) were investigated in vivo by magnetic resonance elastography (MRE), and after surgery by the optical stretcher (OS). MRE was performed in a 3-Tesla clinical MRI scanner and magnitude modulus |G∗|, loss angle φ, storage modulus G′, and loss modulus G′′ were derived. OS experiments measured cellular creep deformation in response to laser-induced step stresses. We used a Kelvin-Voigt model to deduce two parameters related to cellular stiffness (μKV) and cellular viscosity (ηKV) from OS measurements in a time regimen that overlaps with that of MRE. We found that single-cell μKV was correlated with |G∗| (R = 0.962, p < 0.001) and G'' (R = 0.883, p = 0.004) but not G' of the bulk tissue. These results suggest that single-cell stiffness affects tissue viscosity in brain tumors. The observation that viscosity parameters of individual cells and bulk tissue were not correlated suggests that collective mechanical interactions (i.e. emergent effects or cellular unjamming) of many cancer cells, which depend on cellular stiffness, influence the mechanical dissipation behavior of the bulk tissue. Our results are important to understand the emergent rheology of active multiscale compound materials such as brain tumors and its role in disease progression. This journal is
CRIS-Team Scopus Importer:2022-08-03